IMAGE OF CONTEMPORARY BIBLIOGRAPHY OF UNIVERSITY SCIENTIFIC LIBRARY IN CONDITION OF SOCIETY INFORMATIZATION - Polishchuk, Olena B. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article describes the portrait of a modern bibliographer of university‘s libraries in the conditions of society‘s information. The great attention was paid to the intellectual development.